A Combined Experimental and Analytical Approach for the Simulation of the Sound Transmission Loss of Multilayer Glazing Systems. Issue 3 (December 2015) - Ruggeri, Paolo; Peron, Fabio; Granzotto, Nicola; Bonfiglio, Paolo
In order to ensure acoustic comfort of living spaces, nowadays façade systems having high performance are required. Within such context the glazing systems play a key role in achieving high levels of sound insulation. The characteristics of sound insulation of such systems can be determined by analytical methods that make use of experimental characterizations of the physical and mechanical parameters of these systems. In this work a combined experimental and analytical approach for sound transmission loss prediction of glazing systems is presented. In particular, the mechanical properties of monolithic and multilayer glasses with viscoelastic interlayer made of polyvinyl butyral (PVB) are measured using resonance curve method of flexural waves on glass beams with different boundary conditions. In order to achieve reliable input mechanical data (Young's modulus and loss factor), tested beams are characterized in free-free and elastic constraints boundary conditions, respectively. The elastic constrain boundary conditions are realized following the same specifications of ISO Standard 10140 series for larger panels. Starting from the proposed mechanical characterization, the diffuse field sound transmission loss of glass panels has been predicted through an analytical model for solid elastic layers. Results from the above-mentioned procedure are compared with laboratory measurements. From the analysis it will be shown a better accuracy in determining the sound transmission loss of panels when the elastic constrain boundary conditions are applied to the representative beams.